NATURE AND RELATIVE TIMING OF BURIALAND DEFORMATION OF SEDIMENTS AND METASEDIMENTS SOUTH OFTHE INDOSINIAN SUTURE, RATCHABURI THAILAND: IMPLICATIONS FOR FRACTURED BASEMENT POTENTIAL - Sik, Ng How (Bulletin of Earth Sciences of Thailand, 2021)
The relative abundances of the stable isotopes carbon-13 and oxygen-18 in a carbonate cement will change according to the fluid chemistry and temperature in the environment where it forms. Thus, a C-O isotope plot is used to indicate diagenesis history in a carbonate study. The same technique can be used with calcite veins to indicate the ambient environment during vein formation. Veins formed at different times in the subsurface experienced different fluids in the burial environments, thus will show different isotope signatures. Previous isotope studies in Thailand have grouped veins of different orientations under one category. This study classified veins according to their orientations in order to identify the relative timing of vein formation using the contrasting isotope signatures. Calcite veins samples are collected in two quarries in the Ratchaburi region of Thailand, and their respective orientations are measured, and timing relationships indicated by any crosscutting of veins are noted. Respective isotope values are then plotted in a C-O isotope plot and clustered according to vein orientation. Older veins tend to cluster together and are separate from younger vein clusters in the C-O isotope plot. The result is then checked with veins cross-cutting relationship to confirm the reliability of the interpretation. The relative timing of vein formation can be defined reliably with stable isotopes and so used to refine any structural analysis. The C-O isotope trend in Ratchaburi can be used as a comparison of relative temperature. When C-O outputs are compared to isotope results from other regions in Thailand, the result can be used to indirectly define relative positions in the Sibumasu and Indochina plates relative to the distance from the Indosinian suture belt. This isotope approach is also useful in studying diagenetic evolution n subsurface carbonates when only well cuttings are available. With a reliable burial curve to compare to, values from drill cuttings in Permian carbonates be used to estimate the age of the subsurface carbonate and infer a possibility of primary or secondary porosity.